1999
DOI: 10.1016/s0008-6363(98)00216-8
|View full text |Cite
|
Sign up to set email alerts
|

Chronic myocardial infarction in the mouse: cardiac structural and functional change

Abstract: These data provide basic information on changes in cardiac structure and function in mice following chronic coronary artery ligation. They indicate the feasibility of induction of chronic myocardial infarction in this species. Furthermore, they show the similarity of cardiac structural and functional consequences of chronic myocardial infarction in mice to those previously described in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
100
0
4

Year Published

2003
2003
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(117 citation statements)
references
References 17 publications
13
100
0
4
Order By: Relevance
“…First, we demonstrated that cNGR-OG488 labeling was restricted to the BZ and IA at 4 and 7 days after MI with a local advantage of 2.3. Earlier histological observations in this model 10 that are supported by the current TPLSM data showed that the infarct and border zone were highly vascularized at this time. Second, as opposed to the plasma T 1/2 of the cNGR label, the tissue residence time of cNGR label was 9.1 hours, and this could be competed out with unlabeled cNGR, showing reversibility of binding and specificity of the cNGR moiety.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…First, we demonstrated that cNGR-OG488 labeling was restricted to the BZ and IA at 4 and 7 days after MI with a local advantage of 2.3. Earlier histological observations in this model 10 that are supported by the current TPLSM data showed that the infarct and border zone were highly vascularized at this time. Second, as opposed to the plasma T 1/2 of the cNGR label, the tissue residence time of cNGR label was 9.1 hours, and this could be competed out with unlabeled cNGR, showing reversibility of binding and specificity of the cNGR moiety.…”
Section: Discussionsupporting
confidence: 83%
“…10 The wound healing response leads to angiogenesis in the border zone (BZ) and in the infarct area (IA). The IA could clearly be distinguished morphologically and the BZ was the area between the infarcted and the still viable myocardium.…”
Section: Murine Myocardial Infarctionmentioning
confidence: 99%
“…Transverse sections of the heart, which were prepared as previously described, 17 were stained with hematoxylin and eosin or anti-desmin antibody and observed by light microscopy.…”
Section: Histopathological Examinationmentioning
confidence: 99%
“…In two mice myocardial infarction was induced by ligating the left anterior descending (LAD) coronary artery four days before the examination, using published procedures [37].…”
Section: Mouse Preparationmentioning
confidence: 99%